MARINE RESERVOIR AGE CORRECTION FOR THE ANDAMAN BASIN. Issue 5 (1st October 2020) - Raj, Harsh; Bhushan, Ravi; Muruganantham, M; Nambiar, Romi; Dabhi, Ankur J
ABSTRACT: Marine reservoir age is an important component for correction in radiocarbon ( 14 C) dating of marine and coastal samples. 14 C concentration in pre-bomb marine samples of known age are used to derive marine reservoir age of a region. Annually banded coral from Landfall island in the northern Andaman has been analyzed for its 14 C concentration during the pre-bomb period 1948–1951. 14 C age and reservoir effect (∆R) are reported for these pre-bomb coral samples from the northern Andaman region. The mean 14 C age of 331 ± 61 yr BP was obtained for the period 1948–1951 with an average reservoir age correction of –138 ± 61 yr. This reservoir age correction is lowest reported from the northern Indian Ocean. ∆R value of the northern Andaman and the Bay of Bengal appears lower than that of southern Andaman. The ∆R values obtained using mollusk shells and coral from the Andaman region shows large variability. The lower reservoir age correction for the Landfall Island situated in the northern part of the Andaman archipelago, could result due to freshwater flux and reduced upwelling in the region.